2020
DOI: 10.3390/nu12041061
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-Enriched Essential Amino Acids Improve Recovery from Post-Exercise Muscle Damage Independent of Increases in Integrated Myofibrillar Protein Synthesis in Young Men

Abstract: Background: Leucine-enriched essential amino acids (LEAAs) acutely enhance post-exercise myofibrillar protein synthesis (MyoPS), which has been suggested to be important for muscle repair and recovery. However, the ability of LEAAs to concurrently enhance MyoPS and muscle damage recovery in free-living humans has not been studied. Methods: In a randomized, double-blind, placebo-controlled, parallel-group design, twenty recreationally active males consuming a controlled diet (1.2 g/kg/d of protein) were supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 75 publications
4
29
0
Order By: Relevance
“…4A ), this approach may not be sensitive to acute changes caused by nutrition, and further investigation using an intravenous stable isotope tracer approach could be required. However, a recent report has also demonstrated that accelerated recovery of muscle function after resistance exercise achieved using a protein nutrition intervention occurred with no further increase in myoPS rates when assessed over a 96-hour period, which would support the current findings ( 38 ). Mechanistically, postexercise protein ingestion also likely suppresses muscle protein breakdown ( 39 ).…”
Section: Discussionsupporting
confidence: 86%
“…4A ), this approach may not be sensitive to acute changes caused by nutrition, and further investigation using an intravenous stable isotope tracer approach could be required. However, a recent report has also demonstrated that accelerated recovery of muscle function after resistance exercise achieved using a protein nutrition intervention occurred with no further increase in myoPS rates when assessed over a 96-hour period, which would support the current findings ( 38 ). Mechanistically, postexercise protein ingestion also likely suppresses muscle protein breakdown ( 39 ).…”
Section: Discussionsupporting
confidence: 86%
“…Eighteen (54). All subjects were considered healthy and physically active based on responses to the Physical Activity Readiness Questionnaire for Everyone (PARQϩ) and International Physical Activity Questionnaire (iPAQ).…”
Section: Methodsmentioning
confidence: 99%
“…Isoleucine, leucine, and valine, the branched chain amino acids are nutritionally essential and have proved to be beneficial for several disorders [32]. According to a study conducted by Waskiw-Ford et al [5], leucine-enriched EAAs acutely enhance post-exercise myofibrillar protein synthesis which has been suggested to be important for muscle repair and recovery. In the present study, isoleucine ranged from 1.65 to 7. )…”
Section: Rana Et Almentioning
confidence: 99%
“…Amino acids are essential nutrients in diets, prerequisite not only for the synthesis of protein but as precursors for synthesis of many bioactive molecules that participate in the regulation of signaling pathways and metabolism in the body [2,3]. Studies have revealed that a balanced essential amino acid (EAA) formulation is highly anabolic and important for muscle repair and recovery [4,5].…”
Section: Introductionmentioning
confidence: 99%